The use of Malcolm Baldridge method for formulating strategic planning in the technological and vocational education - Suharno Suharno; Sukamto Sukamto; Sutarto Sutarto (REID (Research and Evaluation in Education), 2015)
The article described the results of a study evaluating the performance of Technological and Vocational Education (TVE) by means of Malcolm Baldrige method. The data on the performance was used in order to know its excellence and weakness. Based on the performance excellence and weakness, a competitive strategy could be formulated in order to improve the TVE quality. First, performance measurements by means of Malcolm Baldrige criteria were done on seven study programs from different universities. Second, results of the performance measurements were analyzed and described. With the data resulting from the performance measurements as the basis of the analysis, the excellence and weakness of TVE performance might be found. Third, a strategy was developed. Based on the performance excellence and weakness, a performance improvement strategy might be formulated in order to raise the quality level within the educational process of TVE. The research results indicated that for the performance level the seven universities under measurement achieved scores ranging from 526 to 711 point. These results showed that the performance of study programs in TVE within Indonesia put these study programs into the categories of education leader and of emerging education leader. On the basis of those categories, each study program might formulate its own competitive strategy in order to improve the TVE performance so that the educational process being conducted might also improve in terms of quality level.